Inmigrant women in Logroño and their work status after the mandemic in the rioja community - Díaz Cama, Mª Ángeles (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
From the beginning of the confinement to now, insecurity has skyrocketed in the economic sector in general, placing the most vulnerable social groups such as women in an even more critical state. We will set our sights and objective on the social and insertion work developed with migrant women from La Rioja during the pandemic. For this, a review and analysis of socioeconomic data will be carried out based on the unemployment and employment rates requested as of December 31, 2020, considering the projection for the year 2021. In turn, the work of intervention developed for this group.